The elusive Angelman syndrome critical region. Issue 9 (September 1997) - Trent, R J; Sheffield, L J; Deng, Z M; Kim, W S; Nassif, N T; Ryce, C; Woods, C G; Michaelis, R C; Tarleton, J; Smith, A
Abstract : DNA mapping studies in two families provide further information on the Angelman syndrome critical region, which has recently been defined by the gene UBE3A. The first family has probable familial Angelman syndrome with a maternally imprinted inheritance pattern. A 5 year old girl with this disorder has a 14 year old brother and an 11 year old male cousin who have less typical clinical features. DNA microsatellite analysis has shown that the three share a common segment of the same grandpaternal chromosome 15q11-q13 that overlaps with UBE3A. The child with typical Angelman syndrome has an additional maternal recombination 5' to UBE3A. The second family is a mother and son both of whom have mental retardation but no other features of Angelman syndrome despite an extensive DNA deletion on the telomeric side of UBE3A. Together, the two families identify a region between loci D15S210 and D15S986 which forms part of the Angelman syndrome critical region. A new microsatellite (D15S1234) is described which can be used in place of the LS6-1 marker at locus D15S113.